A carbon-based counter electrode and its preparation and application in fiber dye-sensitized solar cells

By coating the surface of metal wires with a carbon-based thin film and constructing a TiO2 nanotube array, the problems of insufficient conductivity and catalytic activity in fiber dye-sensitized solar cells have been solved, improving photoelectric conversion efficiency and device performance, and promoting industrialization.

CN115188595BActive Publication Date: 2025-01-10FUDAN UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210902676.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-29
Publication Date
2025-01-10
Estimated Expiration
2042-07-29

AI Technical Summary

Technical Problem

In existing fiber dye-sensitized solar cells, carbon nanotube fibers have low electrical conductivity, resulting in poor carrier transport. Platinum wires have smooth surfaces and lack micro-nano rough structures, leading to low catalytic performance and high cost, which limits device performance and production applications.

Method used

Using metal wire as a conductive substrate and covering it with a carbon-based thin film, a carbon-based counter electrode with high conductivity and high catalytic activity is prepared by coating or wrapping process. The fiber dye-sensitized solar cell is constructed by combining TiO2 nanotube array and flexible transparent plastic tube.

Benefits of technology

This improved carrier transport speed, enhanced photoelectric conversion efficiency, reduced fabrication costs, and realized the stability of device performance and the industrialization potential of fiber dye-sensitized solar cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115188595B_ABST
    Figure CN115188595B_ABST
Patent Text Reader

Abstract

The present invention relates to a carbon-based counter electrode and its preparation and application in a fiber dye-sensitized solar cell. A metal wire is used as a conductive substrate, and a carbon-based film is covered on the surface of the metal wire to serve as a fiber counter electrode, which is applied to the fiber dye-sensitized solar cell. The application method is as follows: the fiber counter electrode and a titanium dioxide (TiO2) fiber photoanode fully adsorbed with N719 (di-tetrabutylammonium-bis(isothiocyanato)-bis(2,2'-bipyridine-4,4'-dicarboxyl)ruthenium(II)) dye molecules are placed in a flexible transparent plastic tube, and I ‑ / I3 ‑ As the electrolyte of the redox electron pair, the fiber dye-sensitized solar cell is obtained after the tube mouth is sealed with hot melt adhesive. Compared with the prior art, the present invention prepares a fiber pair electrode with high conductivity and high catalytic activity, thereby obtaining a high-performance fiber dye-sensitized solar cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of photovoltaics, and in particular relates to a carbon-based counter electrode and a preparation method thereof and an application thereof in a fiber dye-sensitized solar cell. Background Art

[0002] With the booming development of wearable electronic products, various types of fabrics have become ideal carriers for integrating functional devices such as sensors, displays, microphones, keyboards, etc. The flexible electronic fabrics prepared by these fabrics make human-computer information interaction more convenient. Such wearable electronic textile devices require a sustainable power source that is both portable and safe. Therefore, fiber-shaped photovoltaic devices, namely fiber solar cells, have attracted more and more attention. According to the classification of working mechanism, fiber solar cells mainly include three major systems: polymer, perovskite and dye-sensitized fiber solar cells. In contrast, fiber dye-sensitized solar cells (FDSSC) have the advantages of low cost, simple preparation, high efficiency, and no inert atmosphere is required in the preparation process, so they have high application value. At present, fiber dye-sensitized solar cells often use carbon nanotube fibers or metal platinum wires as counter electrodes. The nanostructure of carbon nanotube fiber (CNT) enables it to effectively catalyze the redox couple in FDSSC electrolyte (Small, 2015, 11, 2963–2989), but the low conductivity of CNT is not conducive to the transport of carriers, resulting in a sharp decrease in the photoelectric conversion efficiency with the increase of the length of the fiber solar cell, and the device performance is poor; while the metal platinum wire has a high conductivity, but the surface of the platinum wire is relatively smooth and lacks micro-nano rough structure, resulting in fewer active sites, low catalytic performance for the redox couple, and the high price leads to an increase in the preparation cost of dye-sensitized solar cells. These problems have seriously restricted the performance, production and application of fiber dye-sensitized solar cells. Therefore, it is urgent to develop a fiber counter electrode with both high conductivity and high catalytic activity, simple preparation process and low price, as an efficient catalytic redox couple, to improve the carrier transport speed, improve the photoelectric conversion efficiency of longer fiber solar cells, ensure the stability of the device performance during use, and promote the industrialization process of fiber dye-sensitized solar cells. Summary of the invention

[0003] The purpose of the present invention is to overcome the defects of the above-mentioned prior art and to provide a carbon-based counter electrode with high conductivity and high catalytic activity, simple preparation process and low price, as well as its preparation and application in fiber dye-sensitized solar cells.

[0004] The purpose of the present invention can be achieved through the following technical solution: a carbon-based counter electrode, with a metal wire as a conductive substrate, and a layer of carbon-based film covered on the surface of the metal wire.

[0005] Furthermore, the metal wire includes pure metal fiber, alloy wire, metal-plated fiber, and metal wrapped wire; the diameter of the metal wire is 0.1 mm to 1 mm.

[0006] Furthermore, the pure metal includes gold, silver, platinum, copper, titanium, or aluminum; and the alloy wire includes stainless steel.

[0007] Furthermore, the type of the carbon-based film is one of a carbon nanotube film, a graphene film, and a carbon nanotube and graphene mixed film; when the carbon-based film is a carbon nanotube film, the outer diameter of the carbon nanotube is 5nm to 30nm, and the length is 0.1μm to 50μm; when the carbon-based film is a graphene film, the size of the graphene is 0.1μm to 20μm.

[0008] The present invention also provides a method for preparing a carbon-based counter electrode, wherein a flat, smooth, dense, and highly catalytically active carbon-based film is covered on the surface of a metal wire through a continuous preparation process, wherein the continuous preparation process includes a coating process or a wrapping process.

[0009] Specifically, the coating process includes unwinding, sizing, drying, and winding, that is, a commercially available carbon nanotube dispersion is used as a slurry, the mass fraction of the slurry is 10%-30%, and the metal wire is unwound and passed through the slurry at a speed of 0.5m / min-10m / min, the drying temperature is 150℃-220℃, and the film thickness is 2μm-50μm;

[0010] The wrapping process includes unwinding, wire drawing, winding and rewinding; that is, wrapping a commercially available carbon-based film on the surface of a metal wire, with a winding speed of 0.5m / min to 5m / min and a winding pitch of 50μm to 150μm.

[0011] The present invention also provides an application of a carbon-based counter electrode in a fiber dye-sensitized solar cell, and the application method is as follows:

[0012] Step (1): vertically growing a TiO2 nanotube array on the surface of a clean titanium wire by an anodic oxidation method, then annealing at 500°C in an air atmosphere, and finally soaking in a N719 dye solution for 12 to 72 hours to prepare a fiber photoanode;

[0013] Step (2): Place the carbon-based counter electrode and the fiber photoanode together in a flexible transparent plastic tube, leaving an appropriate length (generally 1-5 cm) of the two electrodes outside the tube, and inject I - / I 3- The fiber dye-sensitized solar cell device is obtained by sealing the tube mouth with hot melt adhesive as the electrolyte of redox electron pairs.

[0014] Furthermore, in step (1), the diameter of the titanium wire is 0.1 mm to 1 mm;

[0015] The length of the TiO2 nanotube is 10 μm to 40 μm, the outer diameter is 120 nm to 360 nm, the inner diameter is 80 nm to 300 nm, and the wall thickness is 10 nm to 60 nm.

[0016] Furthermore, the material of the flexible transparent plastic tube in step (2) is one of polyethylene or a copolymer of ethylene and other monomers, polytetrafluoroethylene, fluorinated ethylene propylene copolymer, and polycarbonate; the inner diameter of the plastic tube is 0.4 mm to 2 mm, and the tube wall thickness is 0.2 mm to 1 mm.

[0017] Furthermore, the solvent of the electrolyte in step (2) is one or a mixture of acetonitrile, propionitrile, butyronitrile, valeronitrile, glutaronitrile, and 3-methoxypropionitrile;

[0018] The electrolyte in the electrolyte includes iodine, lithium iodide, 1,2-dimethyl-3-propyl imidazolium iodide and 4-tert-butylpyridine, wherein the concentration of iodine element is 0.02M~0.2M, the concentration of lithium iodide is 0.02M~1M, the concentration of 1,2-dimethyl-3-propyl imidazolium iodide is 0.1M~1M, and the concentration of 4-tert-butylpyridine is 0.2M~1.5M.

[0019] Compared with the prior art, the present invention has the following advantages:

[0020] 1. The present invention covers a flat, smooth, dense, and highly catalytically active carbon-based film on the surface of a metal wire through a continuous preparation process, wherein the metal wire is smooth and has high conductivity, and a layer of carbon-based film can be attached to its surface through a conventional coating process and a wrapping process. The prepared carbon-based counter electrode has both high conductivity and high catalytic activity. The metal wire can efficiently transmit carriers, and the carbon-based film can catalyze the oxidation-reduction reaction. 3- / I - The fiber-sensitized solar cells can be prepared by reducing the recombination of electron-hole pairs, electrons and dye molecules, and electrons and electrolytes, thereby improving the performance of the device.

[0021] 2. The carbon-based counter electrode preparation process of the present invention is simple and the materials used are inexpensive, which realizes the large-scale continuous preparation of fiber counter electrodes and is conducive to the industrialization and industrialization of fiber dye-sensitized solar cells. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1Figure (a) is a schematic diagram of the preparation of the carbon-based counter electrode of the present invention and its application in a dye-sensitized solar cell, Figure (b) is a schematic diagram of the structure of the anode in the solar cell, Figure (c) is a schematic diagram of the coating process, and Figure (d) is a schematic diagram of the wrapping process;

[0023] The symbols in the figure are: 1: metal wire 2: carbon-based film 3: photoanode 4: electrolyte 5: packaging tube;

[0024] Figure 2 The middle figure (a) is a photo of the rolled-up carbon nanotube film electrode prepared on a titanium wire substrate based on the coating process prepared in Example 1 of the invention, with a length of several hundred meters. Figure 2 (bc) are scanning electron microscope (SEM) images of the carbon nanotube film / titanium wire counter electrode prepared in Example 1 of the present invention;

[0025] Figure 3 The scanning electron microscope (SEM) images of the nanotube film / titanium wire counter electrode prepared in Example 2 of the present invention are shown in Figure (a) and Figure (bc) are partial enlarged images.

[0026] Figure 4 The current density-voltage relationship curve of the fiber dye-sensitized solar cell prepared in Example 1 of the present invention;

[0027] Figure 5 This is the current density-voltage relationship curve of the fiber dye-sensitized solar cell prepared in Example 2 of the present invention.

[0028] Figure 6 This is the current density-voltage relationship curve of the fiber dye-sensitized solar cell prepared in Example 3 of the present invention.

[0029] Figure 7 This is the current density-voltage relationship curve of the fiber dye-sensitized solar cell prepared in Example 4 of the present invention. DETAILED DESCRIPTION

[0030] The present invention will be described in detail below with reference to the accompanying drawings and embodiments. It should be noted that, for those skilled in the art, several changes and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

[0031] In the present invention, room temperature refers to an ambient temperature of 10°C to 30°C.

[0032] The reagents used in the following examples are all purchased reagents, among which various solvents, dyes, electrolytes, etc. are all purchased from Sinopharm Group Chemical Reagent Co., Ltd. The various equipment used in the following examples are all commercially available equipment.

[0033] Example 1

[0034] See also Figure 1 (c) The preparation steps of the high conductivity carbon-based counter electrode are:

[0035] A carbon nanotube dispersion with a mass fraction of 15% was selected, and a titanium wire with a diameter of 0.2 mm was unwound, slurried, dried and reeled through a horizontal coating process. The reeling speed was 9 m / min and the drying temperature was 150°C. A flat, smooth and dense carbon nanotube film with a thickness of 10 μm was continuously prepared on the surface of the titanium wire, and the carbon nanotube film / titanium wire counter electrode was completed.

[0036] The photo of the rolled carbon nanotube film / titanium wire counter electrode prepared in this example is shown in FIG. Figure 2 (a) shows that the length is hundreds of meters. The microscopic morphology of the counter electrode coated with carbon nanotube film is shown in Figure 2 As shown in (b-c), the carbon nanotube film is smooth, flat and dense.

[0037] The carbon nanotube film / titanium wire is used as a counter electrode and applied to a fiber dye-sensitized solar cell. The preparation method is as follows:

[0038] Step (1): ultrasonically clean a 0.12 mm titanium wire with acetone, isopropanol and deionized water in sequence and dry it, then vertically grow a titanium dioxide nanotube array on the surface of the titanium wire by anodization (prepared by the anodization method reported in reference J. Mater. Chem. A, 2014, 2, 345–349), then anneal at 500°C in an air atmosphere, and then immerse it in a N719 dye solution for 16 hours, and the fiber photoanode is thus prepared;

[0039] Step (2): Place the carbon nanotube film / titanium wire counter electrode and the fiber photoanode prepared in step (1) in parallel in a flexible transparent ethylene-vinyl acetate copolymer (EVA) plastic tube with an inner diameter of 0.6 mm and a tube wall thickness of 0.2 mm, leave an appropriate length of the two electrodes outside the tube, and inject electrolyte. The solvent of the electrolyte is acetonitrile, wherein the concentration of iodine is 0.02M, the concentration of lithium iodide is 0.1M, the concentration of 1,2-dimethyl-3-propyl imidazolium iodide is 0.6M, and the concentration of 4-tert-butylpyridine is 1M. Use hot melt adhesive to seal the tube mouth, and the fiber dye-sensitized solar cell device is completed.

[0040] Figure 4 The current density-voltage relationship curve of the prepared fiber dye-sensitized solar cell was tested under standard sunlight of AM 1.5. The fiber dye-sensitized solar cell was 10 cm long, with an open circuit voltage of 0.759 V and a short circuit current density of 13.995 mA / cm 2, filling factor is 0.714, and energy conversion efficiency is 7.616%, showing excellent device performance.

[0041] Example 2

[0042] See also Figure 1 (d) The preparation steps of the high conductivity carbon-based counter electrode are:

[0043] An oriented carbon nanotube fiber film with a width of 120 μm was selected, and the carbon nanotube fiber film was evenly wrapped on the surface of a titanium wire with a diameter of 0.15 mm through a wrapping process of unwinding, leading, winding, and winding. The winding speed was 1 m / min, the winding pitch was 60 μm, and a flat, smooth, and dense carbon nanotube film with a thickness of 10 μm was continuously prepared on the surface of the titanium wire. The carbon-based fiber counter electrode was thus prepared.

[0044] Figure 3 Figure (a) shows the microscopic morphology of the prepared carbon nanotube film / titanium wire electrode. Figure (bc) shows the local magnified electron microscope image of the carbon nanosheet functional layer. It can be seen that the carbon nanotube film on the surface of the titanium wire is flat, smooth, dense and evenly distributed.

[0045] The carbon nanotube film / titanium wire is used as a counter electrode and applied to a fiber dye-sensitized solar cell. The preparation method is as follows:

[0046] Step (1): ultrasonically clean a 0.12 mm titanium wire with acetone, isopropanol and deionized water in sequence and dry it, then vertically grow a titanium dioxide nanotube array on the surface of the titanium wire by anodization, then anneal at 500°C in an air atmosphere, and then immerse it in a N719 dye solution for 16 hours, and the fiber photoanode is thus prepared;

[0047] Step (2): Place the carbon nanotube film / titanium wire counter electrode and the fiber photoanode prepared in step (1) in parallel in a flexible transparent ethylene-vinyl acetate copolymer (EVA) plastic tube with an inner diameter of 0.6 mm and a tube wall thickness of 0.2 mm, leave an appropriate length of the two electrodes outside the tube, and inject electrolyte. The solvent of the electrolyte is acetonitrile, wherein the concentration of iodine is 0.02M, the concentration of lithium iodide is 0.1M, the concentration of 1,2-dimethyl-3-propyl imidazolium iodide is 0.6M, and the concentration of 4-tert-butylpyridine is 1M. Use hot melt adhesive to seal the tube mouth, and the fiber dye-sensitized solar cell device is completed.

[0048] Figure 5 The fiber dye-sensitized solar cell prepared in this embodiment is tested under standard sunlight of AM 1.5. The fiber dye-sensitized solar cell has a length of 10 cm, an open circuit voltage of 0.766 V, and a short circuit current density of 13.873 mA / cm2 , fill factor 0.714, and energy conversion efficiency 7.589%, showing excellent device performance.

[0049] Example 3

[0050] The preparation steps of high conductivity carbon-based counter electrode are as follows:

[0051] A graphene dispersion with a mass fraction of 20% was selected, and a stainless steel wire with a diameter of 1 mm was unwound, slurried, dried and reeled through a horizontal coating process. The reeling speed was 0.5 m / min and the drying temperature was 220°C. A flat, smooth and dense graphene film with a thickness of 50 μm was continuously prepared on the surface of the stainless steel wire, and the graphene film / stainless steel wire counter electrode was completed.

[0052] The graphene film / stainless steel wire is used as a counter electrode and applied to a fiber dye-sensitized solar cell. The preparation method is as follows:

[0053] Step (1): ultrasonically clean a 1 mm titanium wire with acetone, isopropanol and deionized water in sequence and dry it, then vertically grow a titanium dioxide nanotube array on the surface of the titanium wire by anodization, then anneal at 500 °C in an air atmosphere, and then immerse it in a N719 dye solution for 72 hours, and the fiber photoanode is prepared;

[0054] Step (2): Place the graphene film / stainless steel wire counter electrode and the fiber photoanode prepared in step (1) in parallel in a flexible transparent polytetrafluoroethylene plastic tube with an inner diameter of 2 mm and a tube wall thickness of 1 mm, leave an appropriate length of the two electrodes outside the tube, and inject electrolyte. The solvent of the electrolyte is acetonitrile, wherein the concentration of iodine is 0.2 M, the concentration of lithium iodide is 1 M, the concentration of 1,2-dimethyl-3-propyl imidazolium iodide is 1 M, and the concentration of 4-tert-butylpyridine is 1.5 M. Use hot melt adhesive to seal the tube mouth, and the fiber dye-sensitized solar cell device is completed.

[0055] Figure 6 The fiber dye-sensitized solar cell prepared in this example is tested under standard sunlight of AM 1.5, and the current density-voltage relationship curve is 0.736V and the short-circuit current density is 13.698mA / cm 2 , fill factor 0.761, and energy conversion efficiency 7.678%, showing excellent device performance.

[0056] Example 4

[0057] The preparation steps of high conductivity carbon-based counter electrode are as follows:

[0058] An oriented graphene fiber film with a width of 120 μm was selected, and the graphene fiber film was evenly wrapped on the surface of a silver wire with a diameter of 0.1 mm through a wrapping process of unwinding, leading, winding, and winding. The winding speed was 0.5 m / min, and the winding pitch was 150 μm. A flat, smooth, and dense graphene film with a thickness of 50 μm was continuously prepared on the surface of the silver wire, and the carbon-based fiber counter electrode was completed.

[0059] The graphene film / silver wire is used as a counter electrode and applied to a fiber dye-sensitized solar cell. The preparation method is as follows:

[0060] Step (1): ultrasonically clean a 1 mm titanium wire with acetone, isopropanol and deionized water in sequence and dry it, then vertically grow a titanium dioxide nanotube array on the surface of the titanium wire by anodization, then anneal at 500 °C in an air atmosphere, and then immerse it in a N719 dye solution for 72 hours, and the fiber photoanode is prepared;

[0061] Step (2): Place the graphene film / silver wire counter electrode and the fiber photoanode prepared in step (1) in parallel in a flexible transparent polytetrafluoroethylene plastic tube with an inner diameter of 0.4 mm and a tube wall thickness of 0.2 mm, leave an appropriate length of the two electrodes outside the tube, and inject an electrolyte. The solvent of the electrolyte is acetonitrile, wherein the concentration of iodine is 0.02 M, the concentration of lithium iodide is 0.02 M, the concentration of 1,2-dimethyl-3-propyl imidazolium iodide is 0.1 M, and the concentration of 4-tert-butylpyridine is 0.2 M. Use hot melt adhesive to seal the tube mouth, and the fiber dye-sensitized solar cell device is completed.

[0062] Figure 7 The fiber dye-sensitized solar cell prepared in this example is tested under standard sunlight of AM 1.5. The fiber dye-sensitized solar cell has a length of 10 cm, an open circuit voltage of 0.738 V, and a short circuit current density of 13.902 mA / cm 2 , fill factor 0.763, and energy conversion efficiency 7.839%, showing excellent device performance.

Claims

1. A carbon-based counter electrode, characterized in that: Using metal wire as a conductive substrate, a carbon-based film is covered on the surface of the metal wire; The metal wire includes pure metal fiber, alloy wire, metal-plated fiber, and metal wrapped wire; the diameter of the metal wire is 0.1mm~1mm; the type of the carbon-based film is one of carbon nanotube film, graphene film, and carbon nanotube and graphene mixed film; when the carbon-based film is a carbon nanotube film, the outer diameter of the carbon nanotube is 5nm~30nm, and the length is 0.1μm~50μm; when the carbon-based film is a graphene film, the size of the graphene is 0.1μm~20μm; the carbon-based counter electrode is used in fiber dye-sensitized solar cells.

2. A carbon-based counter electrode according to claim 1, characterized in that: The pure metal includes gold, silver, platinum, copper, titanium, or aluminum; the alloy wire includes stainless steel.

3. A method for preparing a carbon-based counter electrode as claimed in claim 1, characterized in that: A flat, smooth, dense, and highly catalytically active carbon-based film is covered on the surface of the metal wire through a continuous preparation process, and the continuous preparation process includes a coating process or a wrapping process.

4. The method for preparing a carbon-based counter electrode according to claim 3, characterized in that: The coating process includes unwinding, sizing, drying and winding, the coating speed is 0.5m / min~10m / min, the drying temperature is 150℃~220℃, and the film thickness is 2μm~50μm; The wrapping process includes unwinding, wire drawing, winding and rewinding; the winding speed is 0.5 m / min~5m / min, and the winding pitch is 50μm~150μm.

5. A use of the carbon-based counter electrode as claimed in claim 1 in a fiber dye-sensitized solar cell, characterized in that: The application method is as follows: Step (1): vertically growing a TiO2 nanotube array on the surface of a clean titanium wire by an anodic oxidation method, then annealing at 500°C in an air atmosphere, and finally immersing the wire in a N719 dye solution for 12h to 72h, thereby preparing a fiber photoanode; Step (2): Place the carbon-based counter electrode and the fiber photoanode together in a flexible transparent plastic tube, leaving an appropriate length of the two electrodes outside the tube, and inject I - / I 3- The fiber dye-sensitized solar cell device is obtained by sealing the tube mouth with hot melt adhesive as the electrolyte of redox electron pairs.

6. The use of the carbon-based counter electrode in a fiber dye-sensitized solar cell according to claim 5, characterized in that: In step (1), the diameter of the titanium wire is 0.1 mm to 1 mm; The length of TiO2 nanotubes is 10μm~40μm, the outer diameter is 120nm~360nm, the inner diameter is 80nm~300nm, and the wall thickness is 10nm~60nm.

7. The use of the carbon-based counter electrode in a fiber dye-sensitized solar cell according to claim 5, characterized in that: The material of the flexible transparent plastic tube in step (2) is one of polyethylene or a copolymer of ethylene and other monomers, polytetrafluoroethylene, fluorinated ethylene propylene copolymer, and polycarbonate; the inner diameter of the plastic tube is 0.4 mm to 2 mm, and the wall thickness is 0.2 mm to 1 mm.

8. The use of the carbon-based counter electrode in a fiber dye-sensitized solar cell according to claim 5, characterized in that: The solvent of the electrolyte in step (2) is one or a mixture of acetonitrile, propionitrile, butyronitrile, valeronitrile, glutaronitrile, and 3-methoxypropionitrile; The electrolyte in the electrolyte includes iodine, lithium iodide, 1,2-dimethyl-3-propylimidazolium iodide and 4-tert-butylpyridine, wherein the concentration of iodine element is 0.02M~0.2M, the concentration of lithium iodide is 0.02M~1M, the concentration of 1,2-dimethyl-3-propylimidazolium iodide is 0.1M~1M, and the concentration of 4-tert-butylpyridine is 0.2M~1.5M.

Citation Information

Patent Citations

  • Light anode and flexile solar battery thereof

    CN101719421A

  • Preparation method for high-performance linear dye-sensitized solar cell

    CN102522216A